Fredholm boundary- value problems with parameter in Sobolev— Slobodetsky spaces - Mikhailets, V.A.; Skorobohach, T.B. (Reports of the National Academy of Sciences of Ukraine, 2021)
The solutions of linear boundary-value problems for systems of ordinary differential equations, which belong to a given Sobolev —Slobodetsky space Wsp , 1 ≤ p <∞, s >1, are studied. Necessary and sufficient conditions for their continuity in a parameter are found. The applications to multipoint boundary-value problems are obtained.